Figs 48–52 in Coccolithophorids in Polar Waters: Wigwamma spp. Revisited ... - Thomsen, Helge A.; Østergaard and Mikal Heldal, Jette B. (Zenodo, 2013)
Figs 48–52. Combination cells involving Pseudowigwamma scenozonion cfr. and an unidentified taxon. TEM whole mounts (Arctic / NEW). 48–49 – combination coccosphere; details of the scale types involved are shown in Fig. 49; 50–52 – partly complete cell (one flagellum missing) of the umineralized counterpart; details of the scales are shown in Fig. 50 (reversed printing) and Fig. 52. ... : Published as part of Thomsen, Helge A. & Østergaard and Mikal Heldal, Jette B., 2013, Coccolithophorids in Polar Waters: Wigwamma spp. Revisited, pp. 237-256 in Acta Protozoologica 52 on page 253, DOI: 10.4467/16890027AP.14.007.1444, http://zenodo.org/record/13193273 ...